Assessing impact of hunting mammals in Alto Itaya river basin, Peruvian Amazon - Aquino, Rolando (2007)
This work report information about of the abundance, hunting pressure and hunting impact on mammal’s populations inhabits forests of the Alto Itaya river basin. Information was collected from censuses of transects and hunting records, carried out in six communities. The Woolly Monkey (Lagothrix poeppigii Schinz) was the most abundant with 15,4 individuals/km², while the red howler monkey (Alouatta seniculus Linnaeus) and the Red-brocket Deer (Mazama americana Erxleben) were the less abundant with 0,15 individuals/km² and 0,5 individuals/km2, respectively. On the other hand, the hunting records show an average annual harvest of 1176 mammals, equivalent to 14184,6 kg. Finally, the harvest model suggests over-hunting of tapir (Tapirus terrestris Linnaeus), White-lipped Peccary (Tayassu pecari Link), Woolly Monkey (L. poeppigii), Red Howler Monkey (A. seniculus) and Black Capuchin Monkey (Cebus apella Linnaeus); for these species, harvest reached in some cases 100% of the annual production.